Decreasing Negative Delivery Risk Influence on the Recepient's Firm Value: Porfolio Approach - Michalski, Grzegorz (Propozycja zastosowania teorii portfela do obniżenia negatywnego wpływu ryzyka dostaw na wartość firmy odbiorcy, 2009)
The basic financial purpose of an enterprise is maximization of its value. Inventory management should also contribute to realization of this fundamental aim. Many of the current asset management models that are found in financial management literature assume book profit maximization as the basic financial purpose. (fragment of text)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 48, s. 557-565